Ambient Temperature and the Air Quality Health Index - Mieczysław Szyszkowicz (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2017)
The Air Quality Health Index (AQHI) [1] was introduced in Canada to represent a summary measure of ambient air pollution and air health effects. The AQHI is primarily applied to inform the Canadian public of health risks associated with ambient air pollution. It is used as a scaled indicator of the environmental health risk. The AQHI is calculated hourly based on a formula that uses the rolling three-hour average concentration levels of three air pollutants. These are the gases: ozone (O3) at ground level, nitrogen dioxide (NO2), and particulate matter (PM2.5 - particles of air pollutants with a diameter of 2.5 micrometers or less). The formula used to calculate the index is as follows: AQHI=(100*10/10.4)*(exp(0.000537*[O3])+exp(0.000487*[PM2.5]) + exp(0.000871*[NO2]) - 3) The AQHI value is defi ned based on the relative risk of mortality associated with these three air pollutants. The coeffi cients in the above formula were estimated using the relation between acute increases in air pollution and associations with increased risk of death as determined using data from major cities across Canada [1]. Various combinations of air polutants were realized to determine such indices[2]. In China, the index is based on PM10 (particles of air pollutants with a diameter not greater than 10 micrometers) and NO2 [3,4]; the Russian index incorporates formaldehyde, carbon monoxide (CO) and total suspended particles (TSP) [5]. Air pollutants such as PM10, sulphur dioxide (SO2) and NO2 are used in the European regional index [6]. The values of the AQHI are reported hourly on a scale of 1 - 10+. The AQHI provides air quality and health risk information using only a single number. Its values on web pages are often represented by colours ranging from light blue (1, no risk) to dark brown (10+, very high risk). The values can be used to implement health protective behaviours (reduce and/or change and/or reschedule outdoor activity) and decrease exposure to ambient air pollution.